Photochromic Potassium Channel Blockers: Design and Electrophysiological Characterization - Mourot, Alexandre (Methods Mol Biol, 2013)
Voltage-gated potassium (K(v)) channels are membrane proteins that open a selective pore upon membrane depolarization, allowing K(+) ions to flow down their electrochemical gradient. In neurons, K(v) channels play a key role in repolarizing the membrane potential during the falling phase of the action potential, often resulting in an after hyperpolarization. Opening of K(v) channels results in a decrease of cellular excitability, whereas closing (or pharmacological block) has the opposite effect, increased excitability. We have developed a series of photosensitive blockers for K(v) channels that enable reversible, optical regulation of potassium ion flow. Such molecules can be used for remote control of neuronal excitability using light as an on/off switch. Here we describe the design and electrophysiological characterization of photochromic blockers of ion channels. Our focus is on K(v) channels but in principle, the techniques described here can be applied to other ion channels and signaling proteins.